Pengenalan Tenun Lurik Melalui Motion Comic “Nurika” di SD Negeri Mijipinilihan Surakarta - Yudi Wibowo; Zaidan Ramadan Ilyas; Andina Aulia Agustin (Universitas Sahid Surakarta, 2026)
Indonesia boasts a rich cultural heritage, notable for the lurik woven fabric that comes from Central Java and Yogyakarta. Nonetheless, the present generation of youth is beginning to value local cultural traditions because of the restricted access to engaging and pertinent educational resources, particularly in elementary education. At SDN Mijipinilihan, the teaching and learning process has yet to fully incorporate the understanding of lurik weaving culture. This challenge requires an inventive strategy that can effectively link children's experiences with local cultural principles. This community service endeavor aims to enhance students' comprehension and appreciation of local cultural heritage by developing digital learning materials inspired by motion comics. The project was executed as a motion comic named